2021
DOI: 10.1063/5.0050263
|View full text |Cite
|
Sign up to set email alerts
|

Metal–insulator transition in RNiO3 (R = Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er) induced by Li doping: A first-principles study

Abstract: Rare earth nickelates (RNOs) have been extensively studied in recent decades because of the metal–insulator phase transition, which can be driven by chemical doping. In the present study, we apply the first-principles calculation to investigate the electronic structures, optical properties, and migration behaviors of Li-doped RNO. Results show that when the doping ratio reaches 100%, RNO changes from the metallic state into an insulating state, which is confirmed by the experimental report. Regarding the optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This adjustment influences the exchange splitting between occupied and unoccupied eigenstates. DFT+U methodologies have proven instrumental in elucidating phenomena such as metal to insulator transitions triggered H/Li doping. , Impressively, the theoretical predictions closely align with experimental observations, highlighting the capability of DFT+U to capture complex and subtle material behavior.…”
Section: Theoretical Models To Study Proton-induced Neuromorphic Beha...mentioning
confidence: 68%
“…This adjustment influences the exchange splitting between occupied and unoccupied eigenstates. DFT+U methodologies have proven instrumental in elucidating phenomena such as metal to insulator transitions triggered H/Li doping. , Impressively, the theoretical predictions closely align with experimental observations, highlighting the capability of DFT+U to capture complex and subtle material behavior.…”
Section: Theoretical Models To Study Proton-induced Neuromorphic Beha...mentioning
confidence: 68%
“…The DFT+U capabilities have been extensively used for predicting lattice parameters, magnetic moments, bandgap for transition metal oxides, [154,155] transition metal sulfides, [156][157][158] transition metal nitrides, [159] rareearth nickelates [160][161][162][163] with a single value of U. Additionally, in case of rareearth nickelates, DFT+U has also been used to study H/Li induced metal-insulator transition which is found to be in agreement with the experi ment. [164][165][166][167] The main limitation of DFT+U approach lies in finding reasonable estimates of the value of U for a particular system. The U parameter can generally be calculated using a selfconsistent basis set in an independent way.…”
Section: Electronic Structure Calculations Of Stable and Metastable P...mentioning
confidence: 99%
“…In these systems, Kotiuga et al and Cui et al respectively studied the effects of oxygen vacancies and Li doping in order to drive and understand changes in electronic structure that give rise to an improved memory device. 57,58 A mechanistic understanding of the interplay between electronic structure changes and magnetic states was provided by computational investigations that could then be used to interpret experiments.…”
Section: A Metal-insulator Transitions In Quantum Materialsmentioning
confidence: 99%